DETERMINANT FACTORS RELATED TO THE INCIDENT OF STUNTING IN CHILDREN AGED 24-59 MONTHS IN ALAI SELATAN VILLAGE WORKING AREA OF ALAI PUSKESMAS UPT MERANTI ISLAND DISTRICT - Rahma Usfita Sari; Nur Afrinis; Fitri Apriyanti; Eka Rosifita Rizqi; Zurrahmi (JURNAL KESMAS DAN GIZI (JKG), 2023)
Stunting is a condition of hindered child growth, which can be attributed to various factors, including a history of low birth weight (LBW), exclusive breastfeeding practices, and the cleanliness of the environment. The primary objective of this research is to pinpoint the factors associated with stunting among children aged 24-59 months in South Alai Village, which falls under the jurisdiction of UPT Puskesmas Alai in Kepulauan Meranti Regency. The data collection period for this study spanned from May 29 to June 20, 2023, and it involved the use of questionnaires and stadiometer measurements. The research design is analytical, utilizing a cross-sectional approach, with data analysis encompassing both univariate and bivariate analyses, including the Chi-Square test.The univariate analysis revealed the following statistics: out of the total sample, 53 toddlers (73%) did not exhibit signs of stunting, 69 toddlers (95%) were never born with LBW, 71 toddlers (97%) received exclusive breastfeeding, and 68 toddlers (93%) resided in environments characterized by satisfactory sanitation conditions. The results of the Chi-Square test, however, indicated that there is no significant relationship between a history of LBW, exclusive breastfeeding practices, environmental sanitation conditions, and the occurrence of stunting (p-value = 1.000).In summary, the majority of children aged 24-59 months in South Alai Village have not experienced LBW, received exclusive breastfeeding, and lived in environments with adequate sanitation. Consequently, there is no noteworthy association between a history of LBW, exclusive breastfeeding practices, environmental sanitation conditions, and the incidence of stunting in these children. The findings from this study are anticipated to enhance mothers' awareness regarding the significance of exclusive breastfeeding practices, appropriate nutrition for children beyond six months of age, and the importance of maintaining a clean environment to prevent the risk of stunting, particularly among toddlers. Mothers of toddlers are encouraged to improve their understanding of stunting, pay attention to their child's nutritional status, and regularly take their toddler to the local integrated health post (Posyandu) for growth and developmental monitoring.